2020
DOI: 10.1111/rec.13152
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effect of mowing on the restoration of Pannonian sand grassland to replace invasive black locust plantation

Abstract: Invasive species are among the main threats to grassland biodiversity, and nature conservation management seeks the best methods to eliminate them and to restore natural habitats. We studied the long‐term effect of mowing on the restoration of Pannonian sand grassland after elimination of invasive black locust (Robinia pseudo‐acacia) plantation in Hungary, Europe. Stands of R. pseudo‐acacia at three sites were felled and stumps herbicide‐treated in the winter of 1994–1995. Mowing with hay removal treatment was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Key issues explored in the Special Issue include grazing (Blackburn et al 2021 b ), fire, mowing, land‐use legacies (nitrogen deposition, weed invasion), soil seed banks (Valkó et al 2021), and abandonment of disturbance (Hernandez et al 2021; Price et al 2021; Reis et al 2021; Valkó et al 2021; Blackburn et al 2021 b ). Although restored grasslands have a disturbance requirement, optimal management may differ in restored grasslands from reference sites due to differences in species composition, land‐use legacies, weed invasions, or other factors.…”
Section: Disturbance and Land‐use Legacies In Restorationmentioning
confidence: 99%
See 4 more Smart Citations
“…Key issues explored in the Special Issue include grazing (Blackburn et al 2021 b ), fire, mowing, land‐use legacies (nitrogen deposition, weed invasion), soil seed banks (Valkó et al 2021), and abandonment of disturbance (Hernandez et al 2021; Price et al 2021; Reis et al 2021; Valkó et al 2021; Blackburn et al 2021 b ). Although restored grasslands have a disturbance requirement, optimal management may differ in restored grasslands from reference sites due to differences in species composition, land‐use legacies, weed invasions, or other factors.…”
Section: Disturbance and Land‐use Legacies In Restorationmentioning
confidence: 99%
“…Generally, some disturbance is necessary in restored grassland assemblages to promote native target species and reduce exotic species. For example, Reis et al (2021) reported that mowing promoted native grassland species and eliminated a woody weed (in combination with herbicide), whereas dense woody cover developed in unmown plots. Assis et al (2021) also found disturbance was required to reduce exotic grasses in Cerrado grasslands.…”
Section: Disturbance and Land‐use Legacies In Restorationmentioning
confidence: 99%
See 3 more Smart Citations